Analisis kemampuan penalaran matematis siswa dengan pendekatan realistic mathematics education pada materi barisan dan deret - Rosliana Siregar; Syahidatul Nadila Lubis (Journal of Didactic Mathematics, 2022)
This study aims to describe and analyze the mathematical reasoning abilities of high school students with the Realistic Mathematics Education (RME) approach in the material of sequences and series. The RME approach in this study was applied in the form of RME reasoning questions. This research uses a descriptive qualitative research method. The subjects in this study were 33 students of class IX-E SMA, then reduction was made by taking three students, one with high, medium, and low reasoning abilities. The data was collected using an instrument of mathematical reasoning ability test in the form of an essay consisting of 4 valid and reliable questions, and by using interviews to obtain data in the form of student responses directly by providing a series of questions posed by the researcher to the subject. Based on the results of the study, several conclusions were obtained that the three subjects had a fairly good understanding of using questions that were close to examples in everyday life. Students who have high reasoning ability are able to master the five indicators of mathematical reasoning ability. Students who have moderate reasoning ability are only able to master three indicators of mathematical reasoning ability. Students who have low reasoning ability, are able to master one hand of mathematical reasoning ability.